Estimation of the interaction of oxidized graphene with rat's erythrocyte membranes and blood plasma proteins by the method of spin probes - Kartel, N.T.; Ivanov, L.V.; Karachevtsev, V.A.; Lyapunov, A.N.; Nardid, O.A.; Cherkashina, Ya.O.; Leontiev, V.S.; Ivanov, А.Yu. (Reports of the National Academy of Sciences of Ukraine, 2017)
The effect of oxidized graphene on the microviscosity of erythrocyte membranes, as well as the viscosity of the water-protein plasma phase, is studied by the spin probe method. The introduction of oxidized graphene into a suspension of erythrocytes did not lead to significant changes in the microviscosity of their membranes. After four hours of incubation, an insignificant increase in the microviscosity is observed, apparently due to the sorption of oxidized graphene on membranes. The obtained results indicate the stability of the structure of erythrocyte membranes upon the interaction with oxidized graphene, which can be considered a sufficiently cytocompatible material. The introduction of oxidized graphene into plasma leads to a gradual increase in the viscosity of the water-protein phase from the macromolecules of serum albumin and other plasma proteins within the first 24 hours. The obtained data confirm the insignificant cytotoxicity of oxidized graphene in comparison with carbon nanotubes, which are able to significantly increase the membrane microviscosity of erythrocyte and break their integrity.